A Study on Employee Motivation in Private School: A Case of Bethany Boarding Higher Secondary School (BHSS) Pokhara - Sharma, Devilal (Journal of Nepalese Business Studies, 2016)
Managing human resource plays a crucial role in the process of organization’s effectiveness. One of the most important functions of HRM is motivation. However, because of complex nature of human behavior, motivation is not easy to understand and use. It is represented by author such as Maslow, McClelland and Herzberg. While some motivation theories try to find out how motivation occurs. Vroom, Adams, Locke and Lantham created the most influential process. The aim of this paper is to find out which motivation factors can effectively increase employee motivation, to know the provided incentives are sufficient or not and the effect of incentives in their performance. This study has suggested that promotion system of the career development is needed to satisfy and motivate the employee. Moreover, the work recognition should create the feeling of they are worth for the organization. The information gained from this paper might be a good starting point for creating motivating systems for existing employees and for new comers. This research was conducted to find out the motivational factors and its effect on employee performance of Bethany Higher Secondary School. Researcher developed a survey questionnaire and distributed to get the view of all the employees. All the responses were analyzed and found that monetary and non-monetary incentives are used to motivate workforce. Good salary and allowances has been used as monetary motivators. While, good working environment, freedom to work and recognition conduct the plan differently and effectively as non-monetary motivator. Journal of Nepalese Business Studies Vol. 9, No. 1, 2015 pp. 91-101